The Role of Physical Education in the Professional Activity of Future Nurses - Asatxonova Dilshoda Azimjon qizi, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article highlights the role and importance of physical education in the professional activities of future nurses. It explains that nursing requires physical endurance, strength, agility, and emotional stability in daily work. The article analyzes how regular physical exercise helps prevent occupational fatigue, strengthen health, and improve work efficiency. It also emphasizes the significance of physical education in promoting a healthy lifestyle. The conclusion states that physical education is an essential factor in effectively preparing future nurses for their professional careers.